2015
DOI: 10.1177/1535370215589051
|View full text |Cite
|
Sign up to set email alerts
|

Human miR-3145 inhibits influenza A viruses replication by targeting and silencing viral PB1 gene

Abstract: MicroRNAs (miRNAs) play an important role in the regulation of gene expression and are involved in many cellular processes including inhibition of viral replication in infected cells. In this study, three subtypes of influenza A viruses (pH1N1, H5N1 and H3N2) were analyzed to identify candidate human miRNAs targeting and silencing viral genes expression. Candidate human miRNAs were predicted by miRBase and RNAhybrid based on minimum free energy (MFE) and hybridization patterns between human miRNAs and viral ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 23 publications
1
48
0
Order By: Relevance
“…1 ), suggesting an alternative mechanism of regulation. Changes in viral replication upon miRNA modulation were modest but consequential as has been shown with several other studies 35 , 36 , 57 60 . In this study, we show that miR-134 interacts with nts 472–492 in the domain V of Sabin-1 5′UTR.…”
Section: Discussionsupporting
confidence: 82%
“…1 ), suggesting an alternative mechanism of regulation. Changes in viral replication upon miRNA modulation were modest but consequential as has been shown with several other studies 35 , 36 , 57 60 . In this study, we show that miR-134 interacts with nts 472–492 in the domain V of Sabin-1 5′UTR.…”
Section: Discussionsupporting
confidence: 82%
“…miRNAs can also bind to negative-strand RNA viruses after transcription of the negative-strand RNA genome into the positive-sense RNA intermediate needed for virus replication. For instance, miR-323, miR-491, miR-485, miR-654, and miR-3145 have been shown to bind to the coding region of the influenza PB1 gene segment leading to RNA degradation in infected human and canine epithelial cell lines in vitro 12 , 33 , 34 . Similar degradation of virus RNA was found when the miRNA let-7c bound to the 3′ NTR of the influenza matrix protein in human alveolar epithelial A549 cells [35] .…”
Section: Mirna Interactions With the Rna Viral Genomementioning
confidence: 99%
“…In contrast, another report showed that H5N1 downregulated miRNAs, such as miR-584-5p and miR-1249, that target the PB2 gene of the virus and inhibit viral replication (6). In another study, miR-3145 inhibited influenza virus replication by targeting and silencing the PB1 gene (43). All together, these studies along with our results indicate that the host utilizes miRNAs to restrict influenza virus via targeting the most essential genes encoding subunits (PB1 and PB2) of the viral RNA polymerase and that are indispensable for viral replication, suggesting that miRNAs are pivotal in innate immune defense against influenza virus and may be involved in restriction of other RNA viruses.…”
Section: Discussionmentioning
confidence: 94%